PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT ANEKA TAMBANG Tbk PERIODE 2013-2022 - Putri Nasyadilla, Richika; Rahman, Fakung (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of the Current Ratio and Debt to Equity Ratio on Return On Equity at PT Aneka Tambang Tbk for the 2013-2022 period. The independent variables in this research are Current Ratio and Debt to Equity Ratio while the dependent variable used is Return On Equity. This research was conducted using secondary data and quantitative descriptive methods. This research population uses data, namely financial reports, with samples of balance sheets and profit and loss statements for 10 years (2013-2022). The data analysis techniques used are descriptive statistical analysis, classical assumption test, coefficient of determination test, correlation coefficient test, multiple linear regression test and hypothesis testing (t test and F test). The results of this research show that Current Ratio partially has a significant effect on Return On Equity, seen from the significant value greater than 0.05 where the value is 0.023 < 0.05 while the tcount value shows results that are greater than ttable of 2.904 > 1,89458 and the Debt variable to Equity Ratio partially has a significant effect on Return On Equity where the significant value is smaller than 0.05, namely 0.001 < 0.05 and the tvalue shows that it is greater than ttable, namely 5.246 > 1,89458. Meanwhile, simultaneously the Current Ratio and Debt to Equity Ratio have a significant effect on Return On Equity, where the result is a significant value of 0.003 < 0.05 while the Fcount test results show it is greater than Ftable of 15.348 > 4,737.